2016
DOI: 10.3402/jchimp.v6.31054
|View full text |Cite
|
Sign up to set email alerts
|

Potential impact of a bedside procedure service on training procedurally competent hospitalists in a community-based residency program

Abstract: BackgroundThe Society of Hospital Medicine has delineated procedures as one of the core competencies for hospitalists. Little is known about whether exposure to a medical procedure service (MPS) impacts the procedural certification rate in internal medicine trainees in a community hospital training program.ObjectiveTo determine whether or not exposure to an MPS would impact both the number of procedures performed and the rate of resultant certifications in a community hospital internal medicine training progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 16 publications
1
24
0
Order By: Relevance
“…Creation of an MPS places the responsibility of core bedside procedures in the hands of a select group of proceduralists. This strategy streamlines training and assessment of individual procedural competency to meet standards set by SHM 36,46 and improves educational outcomes 47‐49 . MPS could improve clinical outcomes, 12,42,50‐52 including length of stay and cost, while maintaining patient satisfaction, 41 as well as recoup lost revenue from referrals by increasing the volume of procedures done by generalists, 40,49 although no robust data supporting the latter point exists.…”
Section: Discussionmentioning
confidence: 99%
“…Creation of an MPS places the responsibility of core bedside procedures in the hands of a select group of proceduralists. This strategy streamlines training and assessment of individual procedural competency to meet standards set by SHM 36,46 and improves educational outcomes 47‐49 . MPS could improve clinical outcomes, 12,42,50‐52 including length of stay and cost, while maintaining patient satisfaction, 41 as well as recoup lost revenue from referrals by increasing the volume of procedures done by generalists, 40,49 although no robust data supporting the latter point exists.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies described outcomes of attending-led bedside procedure services, but to our knowledge there are no previous reports describing a residentdriven bedside procedure service without routine attending involvement. [6][7][8][9] The RPC increased the total number of procedures available to residents. The availability of ultrasound-guided PIVs resulted in a perceived decrease in the need for more invasive central line insertion with its associated complications.…”
Section: Discussionmentioning
confidence: 99%
“…4 Resident opportunities to perform procedures have diminished, as a number of procedures formerly performed by internists are now being performed by interventional radiologists. 5 In response, some institutions have created attendingrun procedure teams [6][7][8][9] that have been shown to increase the volume of procedures performed, residents' comfort, and self-reported knowledge and competence. 8,9 Significant barriers to starting a procedure service include the financial investment required and the lack of proceduralists to staff the service.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a study by Grover et al, residents in their nal year of training reported performing only 3 thoracenteses throughout the course of their residency 2 . The presence of a facultystaffed procedure service available to offer supervision of resident procedures has been shown to increase the number of procedures performed and signi cantly increase rates of certi cation 10 . In a study by Lucas et al, the mean number of procedure attempts in resident medical services with access to a procedure team was 48% higher than in those without such access 11 .…”
Section: Introductionmentioning
confidence: 99%